2012
DOI: 10.1158/1078-0432.ccr-12-0832
|View full text |Cite
|
Sign up to set email alerts
|

Prospero Homeobox 1 Promotes Epithelial–Mesenchymal Transition in Colon Cancer Cells by Inhibiting E-cadherin via miR-9

Abstract: Purpose: Prospero homeobox 1 (PROX1) has been shown to function as a tumor suppressor in various types of cancer. However, it promotes colon cancer progression. The aim of this study is to clarify the underlying mechanism by which PROX1 regulates tumorigenicity of colon cancer.Experimental Design: Association of PROX1 and clinicopathological features was studied by immunohistochemical staining. Pri-miR-9-2 and miR-9 were detected by quantitative real-time PCR. Assays of cell invasion, adhesion, and matrix meta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 34 publications
(41 reference statements)
5
85
0
2
Order By: Relevance
“…There is increasing evidence that EMT is a major contributor to tumor progression and metastasis and is associated with poor clinical outcomes of various cancers [29,30]. A study [31]. Our study showed that PROX1 knockdown increased the adhesion of gastric cancer cells to ECM proteins and decreased their migration.…”
Section: Discussionsupporting
confidence: 47%
“…There is increasing evidence that EMT is a major contributor to tumor progression and metastasis and is associated with poor clinical outcomes of various cancers [29,30]. A study [31]. Our study showed that PROX1 knockdown increased the adhesion of gastric cancer cells to ECM proteins and decreased their migration.…”
Section: Discussionsupporting
confidence: 47%
“…We found that Prox1 increased miR-9 expression to inhibit E-cadherin and subsequently enhanced cell invasiveness. 16 Importantly, we also found that Prox1 only controlled the expression of miR-9 in colon cancer cells but not HCC cells. One possible explanation is that Prox1 needs to work with other transcription activators or repressors to exert its function.…”
Section: Prox1 Inhibits Proliferation Of Hcc Cells By Inducingmentioning
confidence: 62%
“…Our recent study showed that Prox1 promotes EMT by downregulating E-cadherin expression in colon cancer cells. 16 We also find that Prox1 increases cell invasiveness by regulating integrins and matrix metalloproteinases. Conversely, defective Prox1 function caused by genomic deletion, mutation, and promoter methylation is generally found in breast cancer, hematological these cells (Fig.…”
Section: Introductionmentioning
confidence: 57%
“…The prosurvival protein ZEB1 has been identified as a direct target of miR-200c and miR-141, and ZEB1 is a key molecule involved in the processes of EMT and EndMT that directly suppress E-cadherin (34,40). Downregulation of miR-141 and miR-205 has been implicated in EMT progression, whereas upregulation of miR-21 and miR-9 has been linked to EndMT and EMT, respectively (30,37). Similar expression patterns for these miRNAs (Table 1, Fig.…”
Section: Mir-21 and The Mir-17-92 Clustermentioning
confidence: 99%